Correlation between Selected Micronutrient Status in Maternal Blood and Cord Blood of Newborn from a Tertiary Care Hospital in West Bengal, India: A Cross-sectional Study - Sanjoy Kumar Kunti; Sharmistha Chatterjee; Indranil Chakraborty (Indian Journal of Neonatal Medicine and Research, 2023)
Introduction: The demand for most micronutrients increases during pregnancy for obvious reasons. Micronutrients like copper and zinc are indispensable co-factors for various enzymes in metabolism. The reduction in the concentration of serum iron and ferritin is a common phenomenon in pregnancy, and early diagnosis is crucial for favourable maternal and foetal outcomes. However, there is a dearth of studies on the metabolism of micronutrients in pregnancy. Aim: The aim of this cross-sectional study, conducted from July 2018 to February 2019 in the Department of Gynaecology and Obstetrics and the Department of Biochemistry, College of Medicine and Sagore Dutta Hospital, West Bengal, India, was to assess the serum levels of copper, zinc, and iron in maternal serum and foetal cord blood. Additionally, the study aimed to correlate the concentrations of these micronutrients between maternal serum and foetal cord blood. Materials and Methods: A total of 336 pregnant women of childbearing age, irrespective of gravida, were included in the study. Blood samples were collected from the pregnant women, and cord blood samples were collected from the foetal end in clot vials for the estimation of copper, zinc, and iron levels. Correlation was assessed between the concentration of these micronutrients in maternal serum and cord blood of the newborn. Data normality was determined using the Shapiro-Wilk normality tests, and the significance level was set at p-value ≤0.05. Results: The study included a total of 336 pregnant women in the age group of 18-33 years, with a mean age of 29.72±4.39 years. In maternal serum, the mean concentration of copper was 122.79±33.67 μg/dL, zinc was 78.47±27.62 μg/dL, and iron was 114.5±45.05 μg/dL. In foetal cord blood, the mean concentration of copper was 48.02±16.37 μg/dL, zinc was 75.82±27.64 μg/dL, and iron was 185.30±52.74 μg/dL. The correlation coefficients between maternal serum and foetal cord blood concentrations were statistically significant for zinc and iron (p-value <0.05). Additionally, the correlation was statistically significant for copper (p-value=0.030). The mean concentration of haemoglobin in maternal serum was 10.9±1.96 g/dL, compared to 14.05±2.13 g/dL in cord blood. The mean maternal serum ferritin was 73.53±56.15 μg/L, and the mean cord blood ferritin was 147.21±61.13 μg/L. Conclusion: The study demonstrated a positive correlation between the concentrations of iron and zinc in maternal serum and foetal cord blood, while a negative correlation was observed for copper concentration.